Nonoperative Management of Leaks After Laparoscopic Sleeve Gastrectomy With Endoscopic Stents in a Tertiary Referral Center - Fırat, Özgür; Demir, Halit Batuhan; Sezer, Taylan Özgür; Bozkaya, Halil; Özütemiz, Ömer; Ersin, Sinan (Turkish Journal of Gastroenterology, 2022)
Background: Laparoscopic sleeve gastrectomy (LSG) is a frequently performed operation. Leaks are formidable complications; however,the optimal management of these leaks is controversial.Methods: We retrospectively reviewed the medical records of 15 patients referred to our tertiary center between 2012 and 2016 withleaks after LSG.Results: In 12 patients with whom ongoing leaks were identified, stents were inserted with the intent of definitive therapy. In additionto attempts at source control, percutaneous drainage was carried out for intraabdominal collection in 9 patients and pleural effusionin 4 patients. The length of stay in the intensive care unit was significantly shorter in patients referred earlier or in those without anyintervention.Conclusion: LSG leaks can be treated nonoperatively in well-organized centers under meticulously designed protocols, depending on theclinical condition of the patient.